Sampling and single particle analysis for the chemical characterisation of fine atmospheric particulates: A review. - Elmes, Michele; Gasparon, Massimo (Journal of Environmental Management)
To better understand the potential environmental and human health impacts of fine airborne particulate matter (APM), detailed physical and chemical characterisation is required. The only means to accurately distinguish between the multiple compositions in APM is by single particle analysis. A variety of methods and instruments are available, which range from filter-based sample collection for off-line laboratory analysis to on-line instruments that detect the airborne particles and generate size distribution and chemical data in real time. There are many reasons for sampling particulates in the ambient atmosphere and as a consequence, different measurement strategies and sampling devices are used depending on the scientific objectives and subsequent analytical techniques. This review is designed as a guide to some of the techniques available for the sampling and subsequent chemical analysis of individual inorganic particles.